An Ayurvedic Approach on Habitual Abortion due to Torch Infection w.s.r. to Putraghni Yoni Vyapada: A Case Study - Sulekha; Meena, Narendra Kumar; Dixit, Mahesh (International Research Journal of Ayurveda & Yoga, 2022)
Introduction- Miscarriage is a personal and emotional loss for a young couple trying to start a family. Full-term births are essential for healthy offspring. Recurrent miscarriage is a common problem during childbearing years. Many factors are responsible for recurrent pregnancy loss among which TORCH infection (Toxoplasmosis, Rubella, Cytomegalo virus, Herpes simplex) is an important one. Recurrent pregnancy loss (RPL) is also known as recurrent miscarriage or habitual abortion. It is defined as three consecutive pregnancy losses prior to 20weeks of pregnancy from the last menstrual cycle (LMP). Putraghni is a condition where repeated pregnancy loss occurs because of Artava dosha, Rakta dosha, Ati raktasrava. The article is to understand the habitual abortion caused due to TORCH Infection w.s.r. to Putrghani Yoni vyapada and to study the effect of Ayurvedic medicines in the management of habitual abortion caused due to TORCH Infection. Main observations: We report a case of habitual abortion (Putraghni yoni vyapada) in a 34-year-old female patient with complaint of wants to convince issue along with stress and fear of previous 3 abortions. Result: Ayurvedic remedies were used to treat the patient for three months. This case study demonstrates the efficacy of Ayurvedic treatment for habitual abortion (Putraghni yoni vyapada). Conclusions: In this article, a case of positive TORCH infection with repeated pregnancy loss treated successfully with Ayurvedic medications.